Neuroendocrine tumor and squamous cell carcinoma arising in a tailgut cyst with features of anal canal: Report of a case and review of the literature - Momoko Takizawa; Masamichi Koyama; Mai Iwaya; Takeshi Uehara; Hiroyoshi Ota (Elsevier, 2021)
A tailgut cyst (retrorectal cystic hamartoma) is a rare benign cystic lesion that originates from the fetal gut remnants, and neoplastic transformation has been described. However, a detailed histological examination of non-neoplastic components of the epithelial lining and cyst wall structure of tailgut cysts has not been reported. We report a case of a tailgut cyst which showed anal canal histology and two different epithelial neoplasms: neuroendocrine tumor (NET) and squamous cell carcinoma (SCC). The multilocular cystic lesion with small solid components was resected. Non-neoplastic areas were similar to those of the anal canal (stratified squamous and columnar epithelia, ducts, and mucous glands). Immunoprofiles of the stratified columnar epithelium were consistent with anal transitional zone epithelium. The stratified columnar epithelium, ducts, and mucous glands were immunoreactive with anti-MUC5AC, MUC5B, and SOX2 antibodies. The solid components represented a grade 1 NET and SCC. The NET tissue had the same immunohistochemical profile as L-cell NETs (hindgut derivative), including INSM1(+), synaptophysin(+), chromogranin A(+, focal), GLP-1(+), prostatic acid phosphatase(+), and CDX2(−) immunoreactivity. The SCC showed the same immunoreactivity as anal SCCs: desmoglein-3(+), CK5/6(+), p63(+), and CDX2(+, focal). Immunohistochemistry characterized the tailgut histology and tumor profiles and demonstrated that MUC5AC, SOX2, and desmoglein-3 were especially useful for distinguishing between a tailgut cyst and mature cystic teratoma.